Static Simulation in USD-Based Hedging Transactions for Hajj Funds in the Banking Money Market: Implications for Banking Policy in Indonesia - Ahmad Saifi Athoillah; Mutia Tsalitsa Alawia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aimed to: (a) analyse sharia hedging transactions of hajj funds in sharia banking through static simulation, (b) identify the cost savings obtained, the optimal term and pricing, as well as the appropriate timing and amount of hajj funds, (c) provide recommendations to the BPKH. This study applied a static simulation method with a Sharia hedging scheme utilizing simple forward contracts, along with a comparative analysis of data on 25% of Hajj funds in Islamic Commercial Bank (BUS) accounts for the period 2007-2024. The simulation involved BUS entering into a USD sale and purchased a contract with a Conventional Commercial Bank (BUK), then BUK enters into a SAR sale and purchase contract with a Foreign Bank (BA). Premium calculations used financial indicators as references, including the Islamic Interbank Money Market (PUAS) yield, the Interbank Money Market (PUAB) rate for foreign exchange, and the Saudi Arabia Interbank Offer Night (SAIBON). Based on the Islamic hedging simulation, it was proven that: (i) the optimal period is 12 months because the longer the Islamic hedging period, the greater the cost savings obtained, (ii) the right time to conduct Islamic hedging is when the rupiah weakens against the USD by 20%-30% and 40%-50%, (iii) the inappropriate time is when the rupiah strengthens against the SAR by 10%-20%, (iv) the amount of hajj funds that has the potential to provide optimal cost savings is IDR 2.4 trillion to IDR 2.7 trillion and IDR 5.2 trillion to IDR 8.5 trillion. The results of this study proposed the following to the BPKH: (i) the BPKH is recommended to conduct sharia hedging by considering the right time and the optimal amount of hajj funds, as well as the potential cost savings that can be obtained, (ii) the right time to conduct sharia hedging is when the rupiah weakens against the USD and SAR, while it is not recommended when the rupiah strengthens against the USD and SAR, (iii) the amount of hajj funds that provides maximum cost savings is between Rp 2.4 trillion and Rp 2.7 trillion and between Rp 5.2 trillion and Rp 8.5 trillion, (iv) the optimal period is 12 months. Thus, BPKH needs to monitor fluctuations in the rupiah against the USD and SAR, as well as the returns from money market instruments, before conducting sharia hedging.